Pengaruh Kualitas Audit, Profitabilitas, dan Leverage Terhadap Opini Audit Going Concern (Literature Review) - Wira Eka Banias; Cris Kuntadi (Dinasti Review, 2022)
Abstract: This article aims to determine the effect of audit quality, profitability, and leverage on going concern audit opinions. Literature review articles are made for the purpose of determining hypotheses between variables. The research was conducted using quantitative methods. This article produces research results, namely Audit Quality and Leverage partially have a significant effect on Going Concern Audit Opinion. Profitability and Ownership Structure partially have no effect on the Going Concern Audit Opinion. Audit Quality, Profitability and Leverage simultaneously affect the Going Concern Audit Opinion. Abstrak: Artikel ini bertujuan untuk mengetahui pengaruh kualitas audit, profitabilitas, dan leverage terhadap opini audit going concern. Artikel literatur review dibuat untuk tujuan menentukan hipotesis antar variable. Penelitian dilakukan dengan menggunakan metode kuantitatif. Artikel ini menghasilkan hasil penelitian yaitu Kualitas Audit dan Leverage secara parsial berpengaruh signifikan terhadap Opini Audit Going Concern. Profitabilitas dan Struktur Kepemilikan secara parsial tidak berpengaruh terhadap Opini Audit Going Concern. Kualitas Audit, Profitabilitas dan Leverage secara simultan berpengaruh terhadap Opini Audit Going Concern.